2002
DOI: 10.1016/s0035-9203(02)90306-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Escherichia coli resistance to co-trimoxazole in tuberculosis patients and in relation to co-trimoxazole prophylaxis in Thyolo, Malawi

Abstract: In Thyolo district, Malawi, an operational research study is being conducted on the efficacy and feasibility of co-trimoxazole prophylaxis in preventing deaths in HIV-positive patients with tuberculosis (TB). A series of cross-sectional studies were carried out in 1999 and 2001 to determine (i) whether faecal Escherichia coli resistance to co-trimoxazole in TB patients changed with time, and (ii) whether the resistance pattern was different in HIV-positive TB patients who were taking co-trimoxazole prophylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
0
14
1
1
Order By: Relevance
“…29,32 Since most of these studies were not specifi cally designed with the primary intention of studying drug resistance as a function of prophylaxis, the evidence base is not powerful enough to dismiss the risk of resistance developing, and specifi c ongoing surveillance is therefore justifi ed. The potential problem is not only for increased resistance to co-trimoxazole, which is already high in many settings, but also for worsening resistance to other antibiotics.…”
Section: Barriers Preventing Scale-up Of Co-trimoxazole Prophylaxis Imentioning
confidence: 99%
“…29,32 Since most of these studies were not specifi cally designed with the primary intention of studying drug resistance as a function of prophylaxis, the evidence base is not powerful enough to dismiss the risk of resistance developing, and specifi c ongoing surveillance is therefore justifi ed. The potential problem is not only for increased resistance to co-trimoxazole, which is already high in many settings, but also for worsening resistance to other antibiotics.…”
Section: Barriers Preventing Scale-up Of Co-trimoxazole Prophylaxis Imentioning
confidence: 99%
“…This was similar with the recent observational cohort study done in Moshi, Tanzania on the effect of TMP-SMX prophylaxis on antimicrobial resistance of faecal Escherichia coli in HIV-infected patients. Fifty-seven faecal E. coli isolated from HIV-infected patients that were on TMP-SMX prophylaxis, 37(64.9%) were already resistant to TMP-SMX before the commencement of TMP-SMX prophylaxis (Zachariah et al, 2002). Studies in East Africa and southern Africa have also demonstrated such resistance in Enterobacteriaceae (Murray, 1987;van Oosterhout et al, 2005;WHO, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This was similar with the recent observational cohort study done in Moshi, Tanzania on the effect of TMP-SMX prophylaxis on antimicrobial resistance of feacal Escherichia coli in HIV-infected patients. Out of fifty-seven (57) feacal E. coli isolated from HIV-infected patients that were on TMP-SMX prophylaxis, 37(64.9%) were already resistant to TMP-SMX before the commencement of TMP-SMX prophylaxis (Zachariah et al, 2002). Studies in East Africa and southern Africa have also demonstrated such resistance in Enterobacteriaceae (van Oosterhout et al, 2005;Murray, 1987;WHO, 2007).…”
Section: Discussionmentioning
confidence: 99%